ANALISIS BALANCED SCORECARD SEBAGAI ALAT PENGUKUR KINERJA MANAJEMEN PERUSAHAAN LEASING (Studi Kasus pada PT. Samudra Artha Finance) - Gumanti Gumanti; Bernadhita H. S. Utami (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2021)
Performance assessment is one of the important factors in the company. Apart from being used to assess the success of the company, performance measurement can also be used as a basis for determining the reward system in the company. The Balanced Scorecard is comprehensive enough to motivate executives in realizing performance from these four perspectives so that the resulting financial success is sustainable. Financing through leasing is generally intended for the procurement of capital goods in the form of production facilities and equipment such as machinery and other equipment. Also, the type of business being carried out is consumer financing, which is a financing transaction for the purchase of consumer goods to individuals using a periodic payment system, where the main customer is the general public who has credibility. PT. Samudra Artha Finance is a finance company incorporated in the finance business and solutions for two-wheeled and four-wheeled motor vehicles. The purpose of writing this article is to determine the performance achievements of PT. Samudra Artha Finance. From the results, the assessment using the balanced scorecard greatly facilitates PT. Samudra Artha Finance to be able to find out the advantages and disadvantages of the company. The suitability of the vision and mission so that goal congruence is created among business actors has a very big influence in achieving the overall goals of the company as indicated by a final score of 97.95% or having a good performance.Keywords: balanced scorecard, leasing, assessment, performance